Unearthing the rhetorical significance of Amburukay a sugidanon (epic) of Panay - Jarantilla, Pia K (Diliman, Quezon City University of the Philippines College of Arts and Letters, 2016)
When a discourse becomes useless to society, it will cease to exist. Consequently, its existence shows that it remains to be significant in the lives of the community. By using Bitzer's The Rhetorical Situation and Carey's The Ritual View of Communication, the rhetorical situation of the epic Amburukay of the Panay Bukidnon uncovered the dynamics of how oral tradition is able to adapt through the changing times, and how the discourse remains significant to the Panay Bukidnon. Identifying the rhetorical situation behind the discourse using contextual rhetorical analysis required an hermeneutic phenomenological approach due to the reliance on textual accounts and narratives on the community. Mimesis was used as method to reconstruct the phenomenon portrayed in the texts and narratives collected. The data showed that the exigencies faced by the community changed in form as the community faced different trials but the essence of the need was still based on one thing : survival of the community. The discourse was able to address this need of survival in the past by educating children on the importance and necessity of marriage, as well as upholding traditional ideals, to strengthen the community. At present, the discourse remains to be significant as it aids in the creation of a cultural identity that creates livelihood, protects the community's ancestral land, preserves their indigenous culture, and promotes indigenous identity and pride within and outside the community.
Thesis (B.A. Speech Communication). -- Diliman, Quezon City : University of the Philippines, 2016.